Examining How Contextual Cues Affect the Interpretation and Dissemination of Metaphors in Social Networks - Whitney Syd Thornton (Journal of Linguistics and Communication Studies, 2024)
This paper explores the intricate relationship between contextual cues and the interpretation and dissemination of metaphors in social networks. Utilizing a multi-disciplinary approach that combines insights from linguistics, cognitive psychology, and communication studies, we investigate how various contextual cues, such as visual elements, hashtags, and social signals, shape the way metaphors are understood and spread in digital environments. Through a comprehensive review of literature and analysis of case studies, we highlight the dynamic interplay between metaphor interpretation and dissemination, revealing how the same metaphor can evoke different interpretations and dissemination patterns depending on the surrounding context. Our findings underscore the complexity of metaphorical communication in social networks and its implications for online discourse. We discuss the theoretical and practical implications of our study, emphasizing the importance of considering contextual cues in the effective use of metaphors in social media communication. Finally, we suggest future research directions to further explore the role of contextual cues in metaphorical communication in social networks.